Friendships between men across sexual orientation: The management of sexual difference through humour. (June 2016) - Barrett, Timothy
Drawing upon qualitative interview data examining friendships between men across sexual orientation, this article contributes to our understanding of the management of sexual difference within interpersonal relationships. In seeming contradistinction to substantial bodies of research that emphasise the significance of maintaining boundaries between homosocial and homosexual desire within male friendship relations, research participants commonly subverted socially constructed distinctions between romantic and platonic relationships as a form of humour. While these joking behaviours seemingly challenged the conventional norms and practices of same-sex male friendship, this article contends that they paradoxically expressed and reinforced fixed sexual identities.